Anti-Othellos and postcolonial Others in Izzat and Aastha. Issue 1 (1st August 2021) - Jayakumar, Archana
While Indian cinematic adaptations that attempt to recreate William Shakespeare's Othello have received scholarly attention, practically no work has been done on films that make fleeting references to the source text while questioning its authority. This article aims to fill the gap by presenting two Hindi-language postcolonial adaptations, namely Izzat (1968) and Aastha (1997), that can be read as anti-Othello films. They challenge Shakespeare's status as a colonial icon in independent India by terming his works as 'rotting feudal tales' and by subverting Othello's murder of Desdemona. However, although men of 'low', mixed or ambiguous origins do not kill their wives in these two adaptations, both films still depict the marginalization of caste, class and gender Others. This article will study the tension between these on-screen Others and the anti-Othello stance.